Tb3+/Sm3+ co-doped double perovskite: synthesis, exfoliation and luminescence properties. Issue 46 (19th May 2022) - Bai, Mingjun; Zhang, Ying; Wan, Hao; Chen, Gen; Liu, Xiaohe; Ma, Renzhi
Abstract : Bulk double perovskite K[K1.5 (Tb1− x Sm x )0.5 ]Ta3 O10 achieved multicolour emissions through tailoring the ratio of Tb 3+ /Sm 3+ co-dopants and could be further delaminated into monolayers through a soft-chemistry exfoliation process. Abstract : Tb 3+ /Sm 3+ co-doped double perovskite K[K1.5 (Tb1− x Sm x )0.5 ]Ta3 O10 (denoted as KKT1− x S x TO) was prepared, which exhibited typical Tb 3+ and Sm 3+ photoluminescence emissions and tunable colours. After protonation and subsequent exfoliation processes, unilaminar KT1− x S x TO nanosheets with a lateral size of ∼300 nm and thickness of ∼2.7 nm were obtained.